2017
DOI: 10.1016/j.drudis.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Mu-Opioid receptor biased ligands: A safer and painless discovery of analgesics?

Abstract: Biased activation of G-protein-coupled receptors (GPCRs) is shifting drug discovery efforts and appears promising for the development of safer drugs. The most effective analgesics to treat acute pain are agonists of the μ opioid receptor (μ-OR), a member of the GPCR superfamily. However, the analgesic use of opioid drugs, such as morphine, is hindered by adverse effects. Only a few μ-OR agonists have been reported to selectively activate the G over β-arrestin signaling pathway, resulting in lower gastrointesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 96 publications
1
64
0
2
Order By: Relevance
“…PZM21 is therefore very similar to the prototypic opioid morphine, although in vivo it is less potent. While the current dogma is that, for μ receptor agonists, respiratory depression results from activation of arrestin signalling (see Chan et al ., ; Madariaga‐Mazón et al, ; Roth et al, ; Smith et al, ), there is evidence that signalling through G i /G o is also involved in mediating this behaviour. μ Receptor coupling through G i /G o proteins results in activation of G protein‐activated inwardly rectifying potassium channels (GIRKs) and inhibition of voltage‐gated calcium channels (North and Williams, ; Seward et al, ), and it has been reported that the respiratory depression induced by either DAMGO, applied locally in the ventrolateral medulla, or fentanyl, administered systemically, is attenuated in GIRK2 subunit knockout mice (Montandon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…PZM21 is therefore very similar to the prototypic opioid morphine, although in vivo it is less potent. While the current dogma is that, for μ receptor agonists, respiratory depression results from activation of arrestin signalling (see Chan et al ., ; Madariaga‐Mazón et al, ; Roth et al, ; Smith et al, ), there is evidence that signalling through G i /G o is also involved in mediating this behaviour. μ Receptor coupling through G i /G o proteins results in activation of G protein‐activated inwardly rectifying potassium channels (GIRKs) and inhibition of voltage‐gated calcium channels (North and Williams, ; Seward et al, ), and it has been reported that the respiratory depression induced by either DAMGO, applied locally in the ventrolateral medulla, or fentanyl, administered systemically, is attenuated in GIRK2 subunit knockout mice (Montandon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The first, herkinorin, activates G proteins with negligible recruitment of β-arrestin 2. It is analgesic with markedly decreased tolerance compared to morphine (91). Herkinorin also exhibits less constipation and respiratory depression (92).…”
Section: Biased Agonismmentioning
confidence: 99%
“…Two more biased agonists, TRV130 and PZM21 (93) also appear to cause less respiratory depression and constipation than morphine; however, respiratory effects and tolerance were observed for PZM21 in a recent study (Hill et al, BJP 2018). TRV130 causes less tolerance than morphine when administered repeatedly to rodents and was analgesic when administered intravenously to treat acute pain, in a phase 2 clinical studies (91). However, there have been no studies in chronic pain, which would be helpful for identifying beneficial properties relating to tolerance and OIH.…”
Section: Biased Agonismmentioning
confidence: 99%
“…Due to its high lipophilicity, fentanyl is able to easily cross the blood‐brain barrier (BBB), thus having great potency (between 75 and 200 times more potent than morphine) . Considered as one of the most frequent analgesics, it produces adverse effects such as vomiting, nausea, gastrointestinal constipation, respiratory depression, dependence and tolerance . However, it produces less adverse effects (AEs) than morphine as lower doses are required to obtain similar analgesic effects …”
Section: Introductionmentioning
confidence: 99%
“…3,5 Considered as one of the most frequent analgesics, 3,4 it produces adverse effects such as vomiting, nausea, gastrointestinal constipation, respiratory depression, dependence and tolerance. 6 However, it produces less adverse effects (AEs) than morphine 7 as lower doses are required to obtain similar analgesic effects. 8 When administered in sublingual doses, fentanyl's calculated bioavailability is 54%.…”
Section: Introductionmentioning
confidence: 99%